At-Ṭāhlīl ās-Shārfy līī āl-Kālīmāt āl-Mustā'ārāh mīn āl-'Arābīyyāh īlā āl-Indunīsīyyāh fīī āl-Kutub ād-Dirosiyyāh āl-'Arābīyyāh bīī āl-Mādrāsāh āl-Islāmīyyāh - Robby Jundi Lestari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Arabic textbooks in Islamic schools contain many loanwords from Arabic into Indonesian, which facilitate students’ language acquisition due to their similarity and ease of memorization. Vocabulary mastery is crucial, as its deficiency often poses challenges in learning Arabic. This study analyzes the root words of loanwords and their absorption process in Arabic textbooks. Using a qualitative literature review approach, data were collected through document analysis and examined using content analysis. The findings reveal that most loanwords follow a triliteral root pattern 126 words, followed by triliteral roots with one additional letter 16 words, two additional letters 4 words, and quadriliteral roots 3 words. The absorption process occurs through direct adoption, phonological adaptation, and morphological adaptation. This study contributes to the development of more effective vocabulary teaching methods for Arabic learning. However, it is limited to Arabic textbooks published by the Ministry of Religious Affairs, excluding those from private publishers. Future research is recommended to explore loanwords in Arabic textbooks from private publishers to understand variations in absorption processes and root words, as well as to assess the effectiveness of loanword-based teaching methods in enhancing students’ Arabic vocabulary mastery.